CROSS ANALYSIS OF PROFESSOR – STUDENT EVALUATIONS AND THE LEVEL OF SINCERITY: A STATISTICAL APPROACH - Toro Sarmiento, Stalin David (2018)
In this article, the topic of Teacher Hetero-evaluation is addressed. The objective is to analyze whether the relationship of Teacher Hetero-evaluation is congruent with values and sincerity of students. This academic research is Descriptive and has been done through a Quantitative Approach. The following instruments are used: Hetero-evaluation, Student’s grades, Number of Students, Number of Fails, Fail Rate, Time Period and Subjects, as well as a Values Test. A statistical approach was performed, which includes hypothesis testing, correlations, significant differences and dependency tests. Some of the results show that teacher Hetero-evaluations increase as Students grades increase as well. Moreover there is statistical evidence that explains how number of students failing a course affects negatively Teacher Evaluation Score. Results from Study of Values Test indicate that students register low scores of Religious Value and with a high degree of Economic Value. This evidence may be harmful for the development of transcendental values such as sincerity and honesty. Therefore Hetero-evaluation could be distorted due to fragility of students’ personality.